Shear behavior of reinforced concrete beams with web opening near supports. (March 2022) - Elansary, Ahmed A.; Abdel Aty, Aya A.; Abdalla, Hany A.; Zawam, Mohamed
Abstract: Deterioration of reinforced concrete beam capacity might occur due to introducing web openings to accommodate essential services such as air conditioning, and electricity. These openings might be near supporting columns at locations of maximum shear forces. In this paper, the influence of utilizing web openings near the supports on the behavior of RC beams was experimentally investigated. The enhancement in these beams 'behavior due to strengthening the openings with external Carbon Fibre Reinforced Polymer (CFRP) sheets was estimated. Six RC beams with different opening sizes located near the supports were cast and tested under four-point loading. Crack pattern, deflections, and strains of the six beams were compared to those of a reference solid RC beam without an opening. Experimental load–deflection and shear strength of the tested beams were compared to those predicted from analytical and code equations. The experimental results revealed that introducing large openings reduced the shear capacity of RC beams by up to 35% compared to that of a solid beam. Also, it was concluded that strengthening the web opening with CFRP sheets increased the shear capacity by 21% ∼ 28% compared to similar beams without CFRP.